The complex phenotype of spinocerebellar ataxia type 48 in eight unrelated Italian families. (1st November 2019) - Lieto, M.; Riso, V.; Galatolo, D.; De Michele, G.; Rossi, S.; Barghigiani, M.; Cocozza, S.; Pontillo, G.; Trovato, R.; Saccà, F.; Salvatore, E.; Tessa, A.; et al.
Abstract : Background and purpose: Heterozygous mutations in the STUB1 gene have recently been associated with an autosomal dominant form of spinocerebellar ataxia (SCA) associated with cerebellar cognitive‐affective syndrome (CCAS), named SCA48. Methods: Molecular screening was performed in a cohort of 235 unrelated patients with adult‐onset, autosomal dominant (17) or sporadic (218) cerebellar ataxia, negative for pathological trinucleotide expansions in the common SCAs, FRDA and FXTAS loci, by using targeted multigene panels or whole‐exome sequencing. Bioinformatics analyses, detailed neurological phenotyping and family segregation studies corroborated the pathogenicity of the novel STUB1 mutations. Clinico‐diagnostic findings were reviewed to define the phenotypic spectrum. Results: Eight heterozygous STUB1 mutations were identified, six of which were novel in 11 patients from eight index families, giving an estimated overall frequency of 3.4% (8/235) for SCA48 in our study cohort, rising to 23.5% (4/17) when considering only familial cases. All our SCA48 patients had cerebellar ataxia and dysarthria associated with cerebellar atrophy on brain magnetic resonance imaging; of note, many cases were also associated with parkinsonism, chorea and dystonia. CCAS also occurred frequently, whereas definite signs of pyramidal tract dysfunction and peripheral nervous system involvement were absent. One SCA48 patient presented with hypogonadism, associated with other autoimmune endocrine dysfunctions. Conclusions: Our results support SCA48 as a significant cause of adult‐onset SCA. Besides CCAS, our SCA48 patients often showed movement disorders and other clinical manifestations previously described in SCAR16, linked to biallelic variants in the same gene, thus suggesting a continuous clinical spectrum and significant overlap amongst recessive and dominantly inherited mutations in STUB1 .